Acceptability of Iron- and Zinc-Biofortified Pearl Millet (ICTP-8203)-Based Complementary Foods among Children in an Urban Slum of Mumbai, India - Huey, Samantha Lee; Venkatramanan, Sudha; Udipi, Shobha A.; Finkelstein, Julia Leigh; Ghugre, Padmini; Haas, Jere Douglas; Thakker, Varsha; Thorat, Aparna; Salvi, Ashwini; Kurpad, Anura V.; Mehta, Saurabh (Frontiers in Nutrition, 2017)
Biofortification, a method for increasing micronutrient content of staple crops, is a promising strategy for combating major global health problems such as iron and zinc deficiency. We examined the acceptability of recipes prepared using iron- and zinc-biofortified pearl millet (FeZnPM) (~80 ppm Fe, ~34 ppm Zn, varietal ICTP 8203), compared to conventional pearl millet (CPM) (~20 ppm Fe, ~19 ppm Zn) in preparation for an efficacy trial. Our objective was to examine the acceptability of FeZnPM compared to CPM among young children and mothers living in the urban slums of Mumbai. Standardized traditional feeding program recipes (n=18) were prepared with either FeZnPM or CPM flour. The weight (g) of each food product was measured before and after consumption by children (n=125) and the average grams consumed over a 3-day period were recorded. Mothers (n=60) rated recipes using a 9-point hedonic scale. Mean intakes and hedonic scores of each food product were compared using t-tests across the two types of pearl millet. There were no statistically significant differences in consumption by children (FeZnPM: 25.27 ± 13.0 g; CPM: 21.72 ± 6.90 g) across the food products (p=0.28). Overall mean hedonic scores for all recipes were between 7 to 9 points. CPM products were rated higher overall (8.22 ± 0.28) compared to FeZnPM products (7.95 ± 0.35) (p=0.01). FeZnPM and CPM were similarly consumed and had high hedonic scores, demonstrating high acceptability in this population. These results support using these varieties of pearl millet in a proposed trial (Clinicaltrials.gov ID: NCT02233764; Clinical Trials Registry of India (CTRI), reference number REF/2014/10/007731, CTRI number CTRI/2015/11/006376) testing the efficacy of FeZnPM for improving iron status and growth.